Empresas de coaching em Curitiba - Napoleão, Rosnival Bueno (2015)
This article aims to analyze about the coaching services offered individuals and organizations in the city of Curitiba-PR. With that map the data collected through market research, highlighting the services offered and their methodologies adopted in the application of coaching advice, meaning the organizational level (leadership / team) or individual (self professional achievement and / or personal). So, draw the profile of the services offered by organizations and their professional characteristics. Having the inventory of services available in the city of Curitiba, their characteristics, theoretical concepts and methodologies.